Design and Construction of An Ozone Generator Based on A Resonant Converter - Kitcharoen, Phattarin; Phoaphan, Busayapol; Yutthagowith, Peerawut (My University, 2019)
This paper presents design and construction of the ozone generator based on a resonant converter. Ozone is caused by the combination of 3 oxygen atoms. Ozone gas is widely used in the industry for killing bacteria, viruses, and protozoa. The ozone gas doesn't cause residual pollution. The ozone gas can be produced from corona discharge on the area with high electrical field stress. In this paper, the resonant converter was developed for high voltage generation on coaxial cylindrical electrodes which are utilized to produces ozone gas. The resonant converter divided into 2 parts. The first part is the control circuit and the second part is the power circuit. The power circuit was used to convert AC voltage to AC voltage with other frequencies. Additionally, the converter can generate a square voltage with adjustable frequency for finding the resonant frequency. From the experiment, the resonant converter can produce ozone gas effectively.